Patient Satisfaction Based on Quality of Service and Location - Mardikaningsih, Rahayu (Journal of Islamic Economics Perspectives, 2022)
This paper aims to observe the causes of patient satisfaction based on service quality and location. The population in this study were patients at a health center in West Surabaya with a total sample of 96 respondents. The method of data analysis to determine the effect of service quality and location on patient satisfaction used an analytical tool, namely the multiple linear regression equation. This study found that service quality and location have a role in the formation of patient satisfaction at the puskesmas. This is an important determinant for achieving patient satisfaction. It is the obligation of the puskesmas to provide the best service for the community in the health sector. The results of this study are expected to be material for improving the quality of services in hospitals and become the basis for further research.